Action Recognition and Application of Table Tennis Training Based on IOT Perception. (31st August 2022) - Zhang, Zhijian
Abstract : As the national sport of our country, table tennis focuses on continuous innovation and development. Table tennis is a high-quality sport characterized by fast movement and great flexibility. Unlike other human behaviors, identifying ping pong shots is idiosyncratic and difficult. Table tennis training is extremely important, and correct training can make athletes progress. In this paper, based on the perception of the Internet of Things, the action recognition and application of table tennis training actions are carried out, and the following conclusions are drawn: (1) the training movements of table tennis are relatively complex, which has a great challenge to the action recognition technology. The action recognition technology based on IoT perception can efficiently identify table tennis training actions. (2) Analyze and study the action recognition algorithm based on IoT perception, and propose a higher recognition accuracy and more stable algorithm DTW. (3) Comparing the accuracy, loss rate, and time impact between the algorithm in this paper and the traditional recognition algorithm, it is concluded that the algorithm proposed in this paper has higher accuracy and lower loss rate than the traditional algorithm. And with good stability, it is not affected by the environment and time. The algorithm in this paper is an algorithm with better performance and more worthy of use.